2022
DOI: 10.1111/imr.13087
|View full text |Cite
|
Sign up to set email alerts
|

Immunity at maternal–fetal interface: KIR/HLA (Allo)recognition*

Abstract: Two major types of natural killer cell receptors (NKR) recognize main histocompatibility complex (MHC) class I molecules: the evolutionarily conserved and non-polymorphic, heterodimeric killer C-type lectin-like receptors (KLRs) (CD94/NKG2) and polygenic and highly polymorphic killer immunoglobulin-like receptors (KIRs). Whereas CD94/NKG2 bind to non-classical MHC class Ib molecules, KIRs bind to classical MHC class Ia molecules HLA-A, HLA-B, and HLA-C. MHC in humans is called human leukocyte antigen (HLA) sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 274 publications
0
12
0
Order By: Relevance
“…We have constructed a Sw71‐anembryonic spheroid model from normal immortalized human trophoblast cell line Swan 71 (Sw71) as a surrogate of human blastocyst 13,14 . These Sw71‐spheroids undergo compactization, have morphology and function similar to human blastocyst, and were able to attach to the epithelial endometrial cells, to invade the extracellular matrix and migrate between endometrial stromal cells 15 . However, to fully exploit the applicability of our Sw71 model it must recapitulate the primary trophoblast modalities found in vivo at maternal‐fetal interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have constructed a Sw71‐anembryonic spheroid model from normal immortalized human trophoblast cell line Swan 71 (Sw71) as a surrogate of human blastocyst 13,14 . These Sw71‐spheroids undergo compactization, have morphology and function similar to human blastocyst, and were able to attach to the epithelial endometrial cells, to invade the extracellular matrix and migrate between endometrial stromal cells 15 . However, to fully exploit the applicability of our Sw71 model it must recapitulate the primary trophoblast modalities found in vivo at maternal‐fetal interface.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 These Sw71-spheroids undergo compactization, have morphology and function similar to human blastocyst, and were able to attach to the epithelial endometrial cells, to invade the extracellular matrix and migrate between endometrial stromal cells. 15 However, to fully exploit the applicability of our Sw71 model it must recapitulate the primary trophoblast modalities found in vivo at maternal-fetal interface. Sw71 cell line used in our model has been created more than 10 years ago and was initially characterized as EVT, proven by the expression of epithelial-mesenchymal transition (EMT) markers such as cytokeratin7 (CK7) and vimentin (Vim) as well as by the production of soluble HLA-G. 13,16 The Sw71 trophoblast cell line has been used in several models to test different factors crucial for human implantation.…”
Section: Introductionmentioning
confidence: 99%
“…The HLA‐C molecule is the crucial natural ligand for the killer cell immunoglobulin‐like receptor, thus plays an important role in functional maturation and induction of tolerance in natural killer cells 1,2 . It was reported that the HLA‐C*15:02 allele is common in the Chinese population, with a frequency of 3.33% in the Zhejiang Han population according our previous report 3 .…”
Section: Figurementioning
confidence: 95%
“…HLA‐C molecule serves as a specialized ligand for the killer‐cell immunoglobulin‐like receptors (KIRs) family, which are predominately expressed on the natural killer (NK) cells and some T cells 1 . All known HLA‐C alleles can be classified as C1 or C2 groups based on residue at position 80.…”
Section: Figurementioning
confidence: 99%
“…HLA-C molecule serves as a specialized ligand for the killer-cell immunoglobulin-like receptors (KIRs) family, which are predominately expressed on the natural killer (NK) cells and some T cells. 1 All known HLA-C alleles can be classified as C1 or C2 groups based on residue at position 80. It was reported that KIR2DL1 recognizes HLA-C2 alleles with Lys80 residue, while KIR2DL2 and KIR2DL3 recognize HLA-C1 with an Asn80 residue.…”
mentioning
confidence: 99%